Highly Effective Algorithm of the Threshold Detection in the Cognitive Radio - Qing Long Xu; Zhan Gao (Institute of Advanced Engineering and Science, 2014)
Opportunistic spectrum access (OSA) is a key technique enabling the secondary users (SUs) in a cognitive radio (CR) network to transmit over the “spectrum holes” unoccupied by the primary users (PUs). In contrast to OSA, with spectrum sharing (SS) is allowed to transmit regardless of the PU’s on/off status, provided that the resulting interference to PU is kept below a predefined threshold. In this paper, we focus on the threshold detection algorithm study for spectrum sharing, which aims to get the SIR of the PUs as quickly and precisely as possible. We propose a dichotomy algorithm with lower complexity and more quickly in contrast to the traditional full search algorithm. Numerous simulation results are provided to validate the proposed algorithm. DOI: http://dx.doi.org/10.11591/telkomnika.v12i6.5489